Effect of Smart Tourism Technology Use on Memorable Tourism Experience: The Budapest Sample - BAGDADI, Ali; DÁVID, Lóránt Dénes (Journal of Posthumanism, 2025)
Tourism sector is undergoing major changes due to rapid technological advancements, significantly shaping tourist experiences. Smart tourism technologies – such as digital apps, platforms and services – are transforming how tourists and destinations interact. These tools simplify travel planning, enhance access to information, offer more efficient, personalized experiences. Tourists find easier and more original solutions throughout their journeys, resulting in greater satisfaction and emotional connection to destinations. Positive emotions contribute to memorable travel experiences, which are essential for building lasting tourist-destination relationships. The integration of smart technologies supports not only the improvement of individual experiences but also the sustainable development of tourism destinations. This is especially relevant in the context of circular tourism, which emphasizes long-term value and resource efficiency. This study specifically explores the role of smart tourism technologies in creating unforgettable travel experiences, using Budapest as a case example, highlights their growing importance in the evolving tourism landscape.